Microeconomics of corruption among developing economies - James P. Gander (The University of Utah, Department of Economics, 2011)
A simple micro model of a firm's investment decision made under the uncertainty of the success of a bribe of a government official is developed. The probability of success of the bribe is a function of the amount paid to the official to get things done. The operational model runs the amount of the bribe on such determinants as firm size, country size, shareholder ownership, political instability, and court system. The data covers the periods 2002-2005 and 2006-2010, includes 150 developing countries and has data on some 72,000 firms. Several econometric estimation methods were used. The findings support earlier studies, to wit, firm size and country size are inversely related to the index of corruption. Political instability and the court system were positively related to corruption. Policy implications of the findings are discussed.
Keywords: 330; Firm; Corruption; Uncertainty; Developing Countries